Knowledge and practices regarding pesticide application and handling among farmers in selected community areas of Uttarakhand - kumar, Atul; Pugazhendi, Sanchita; Kumar, Chandan; Davidson, John; Rawat, Jyoti (International Journal of Research in Medical Sciences, 2021)
Background: In South Asia region, India is the biggest country manufacturing pesticides for agricultural production and ranks10th in world where farmers use pesticides in agricultural area. In India, farmers have less knowledge regarding pesticide application and very rarely they get opportunity to attend formal training program regarding handling of hazardous pesticides. In developing countries, farmers have unsafe pesticide application and handling practices due to which pesticide poisoning has a major health problems among famers. Indian farmers who practice unsafe use of pesticides also experience different health problems. Hence there is a necessity to find out knowledge and practices of farmers while handling dangerous pesticides in day to day life. Methods: A quantitative research approach and cross sectional survey design was used in present study. Total of 302 farmers residing in rural area of Doiwala block were selected by using purposive sampling technique. Ethical permission was obtained from institutional ethical committee and informed consent was taken from study participants. Data were analyzed using descriptive statistics. Results: A total of 125 (41.5%) farmers were using pesticide two times in a year and 180(59.8%) farmers used it for protection of crops. It was expressed by 223 (73.8%) farmers that they read the labels on the pesticide containers before using it but only 182(60.3%) farmers followed the instructions on the label. Conclusions: Farmers did not have adequate knowledge about frequency and reasons of using pesticide in farming. Majority of the farmers did not have adequate knowledge and practices regarding use of pesticide in agricultural area.